b - 9; Asiatic Society of Bangladesh (b, 1999)
On the Buddhist sculptures of Bangladesh.
Includes bibliographical references (p. [309]-320) and index.
In Bengali.
Keywords: Buddhist sculpture -- Bangladesh; Buddhist gods, in art